1,2,5-Oxadiazole N-oxide derivatives as potential anti-cancer agents: Synthesis and biological evaluation. Part IV - Boiani, Mariana (2001)
Several new 1,2,5-oxadiazole N-oxide derivatives and some deoxygenated analogues were synthesized to be tested as potential selective hypoxic cell cytotoxins. Compounds prepared were designed in order to gain insight into the mechanism of action of this kind of cytotoxin. Compounds were tested in oxia and hypoxia and they proved to be non-selective. 3-Cyano-N2-oxide-4-phenyl-1,2,5-oxadiazole showed the best cytotoxic activity in oxia. The cytotoxicity observed for these derivatives could be explained in terms of the electronic characteristics of the 1,2,5-oxadiazole substituents. Electrochemical and ESR studies were performed on the more cytotoxic derivative. © 2001 Éditions scientifiques et médicales Elsevier SAS.